Penatalaksanaan Fisioterapi pada Kasus Post Amputasi Transtibial Sinistra Akibat Chronic Limb Ischemia di RSPAD Gatot Soebroto - Pratama, Aditya Denny (UI Scholars Hub, 2018)
Amputation is the removal of a member of the body which involves cutting a part or all of the limb. Problems arising from amputation include surgical wound pain, decreased joint motion, decreased muscle strength, and decreased functional ability. The purpose of this study was to determine physiotherapy interventions in cases of sinistra transtibial amputation due to chronic limb ischemia. This research is a case study conducted at the Gatot Subroto Army Hospital in February-March 2018. Data obtained from interviews, observation, assessment, and management of Physiotherapy. In this case study the limitations of the problem to be discussed are pain, stiffness, spasm, limited scope of joint motion and decreased muscle strength. The modalities that will be applied are Trans Electrical Nerve Stimulation (TENS) and exercise therapy in the form of active motion exercises, stretching, strengthening, and core stability exercises. The results of this case study show that the TENS modality can reduce silent pain, tenderness and motion pain in amputees. Active motion exercises, stretching, strengthening, and core stability exercises can reduce stiffness, spasm, and increase the scope of joint motion and increase muscle strength so as to be able to prepare patients to walk using aids.